A case of severe pneumonia with viremia caused by adenovirus B7 identified by off-label use of a multiplex PCR system. (2021) - Sakakura, Akie; Akashi, Yusaku; Shiigai, Masanari; Isono, Hiroki; Suzuki, Hiromichi; Hirose, Yumi
Abstract: Severe infection with human adenovirus (HAdV) is uncommon in adults, and the lack of reliable point-of-care testing makes the diagnosis challenging. A 39-year-old immunocompetent Indian man developed severe pneumonia, and his condition became life-threatening despite antimicrobial therapy. While sputum and blood cultures remained negative, a multiplex PCR respiratory panel (Filmarray Respiratory Panel), which is only approved for use with nasopharyngeal samples, detected HAdV in the serum and tracheal aspirates on day 5. We therefore initiated ganciclovir, steroids, and intravenous immunoglobulin. The patient's respiratory condition improved significantly, and he eventually recovered without complications. We later confirmed that conventional PCR of serum detected HAdV-B7. Our case illustrated that a respiratory panel using multiplex PCR successfully detected HAdV in unapproved samples. Such off-label analyses may support the early diagnosis of infections caused by pathogens that are difficult to identify by routine microbiological examination.